KETIMPANGAN EKONOMI ANTAR PROVINSI DI SUMATERA - yeniwati, yeniwati (Program Studi Magister Ilmu Ekonomi, 2013)
This research is aimed to identify economic disparity of per capita GRDP at 2000 constant of 10 provinces in Sumatera over period 2005-2010. This study aims to obtain the empirical evidence on (1) influence investment to disparity of economy in Sumatera (2) influence agglomerationÂ to disparity of economy in Sumatera and (3) influence natural resources to disparity of economy in Sumatera. It used secondary and establishment data BPS (IndonesiaÌ•s Bureau Statistic). The methods of analysis are Williamson indeks, OLS (Ordinary Least Square) regression using panel data with method random effect Result of research indicates that, out of 10 provinces in Sumatera, there are 5 provinces have the disparity index bigger than the average of Sumatera and 5 provinces have the disparity index smallerr than the average of Sumatera. While, the result of investment has significant and negative influence to disparity of economy, aglomeration has significant and positive influence to disparity of economy, natural resources have significant and negative influence to disparity of economy